Developing a Competency-Based Arabic Curriculum to Foster Merdeka Belajar in Indonesian Madrasahs - Raswan, Raswan; Husni, Arman; Mudhofir, Ihwan; Qodri, Muhammad; Husein, Sudi Yahya; Muradi, Ahmad; Ashfia, Ahmad (SCAD Independent, 2025)
This study examined the development and implementation of a competency-based Arabic curriculum in Indonesian madrasahs and its implications for students’ learning independence. Employing a qualitative case study design complemented by a descriptive student survey, data were collected through interviews with teachers and principals, classroom observations, and student responses. The findings demonstrated that the curriculum significantly enhanced students’ motivation, enjoyment, and comprehension of Arabic, with 85% reporting greater motivation, 80% increased enjoyment, and 75% improved understanding. Teachers and principals affirmed that the competency-based approach facilitated the design of more relevant materials, clearer assessments, and adaptive teaching strategies, while observations revealed more dynamic student engagement and collaborative learning. Integrating the principles of Merdeka Belajar, the curriculum promoted learner autonomy and contextualized language use, though challenges remained in addressing diverse learning styles and teacher readiness. The study highlighted the novelty of explicitly linking linguistic proficiency with critical thinking, cultural literacy, and real-world application within a faith-based educational context. These insights not only enrich discussions on competency-based education in Islamic schools but also provide a practical model adaptable to other Muslim-majority countries and multilingual environments.